Mechanical design and analysis of a reconfigurable variable stiffness mechanism based on permanent magnetic springs and swing guide mechanism. (March 2023) - Sun, Longfei; Zhao, Wenbo; Wang, Binghao; Huang, Shutao; Li, Jinquan
Stiffness control of an actuator is important to ensure stable contact motion and collision safety for human-robot integration tasks. The variable stiffness mechanism (VSM) is an important part of the variable stiffness actuator. We propose a novel reconfigurable rotational VSM that uses magnet springs and swing guide mechanisms in this paper. Magnet springs are used as elastic elements that are driven by the cable, and the initial stiffness of the mechanism can be regulated by adjusting the air gap distance between the magnets. The mathematical stiffness model of the VSM is developed, and the numerical calculation simulation and experiments are conducted to verify the feasibility of the proposed VSM.